Conservative Therapy of External Invasive Cervical Resorption with Adhesive Systems: A 6-Year Follow-Up Case Report and Literature Review - Riccardo Aiuto; Gianluca Fumei; Erica Lipani; Daniele Garcovich; Mario Dioguardi; Dino Re (Case Reports in Dentistry)
The diagnosis and treatment of external invasive cervical resorption (EICR) could be a challenging clinical situation even for the most experienced dentists. It is a fairly rare lesion and a poorly understood phenomenon, and its insidious and aggressive nature can lead to tooth loss. Even in the era of dental implants, trying to save a compromised tooth is imperative for any clinician. This report presents a case of an upper central incisor with a class II Heithersay EICR in which treatment was performed using a multidisciplinary approach and the defect was restored with resin composite. The surgery in which the defect was exposed and repaired was followed by an endodontic treatment and the placement of a fiber-reinforced post. In this case, the use of modern materials, such as resin composites, allowed not only the avoidance of tooth extraction but also the achievement of satisfactory aesthetic results. The 6-year follow-up demonstrated the success of therapy and the resolution of clinical symptoms. This case report highlights the importance of early detection of EICR and how composite resins could provide an effective and aesthetic restauration of the defect, which favors the health of the surrounding gingival tissue.